Quantitative Label-Free Proteomic Analysis of Milk Fat Globule Membrane in Donkey and Human Milk - Zhang, Xinhao; Jiang, Bo; Ji, Chuanliang; Li, Haijing; Yang, Li; Jiang, Guimiao; Wang, Yantao; Liu, Guangyuan; Liu, Guiqin; Min, Lingjiang; Zhao, Fuwei (Frontiers in Nutrition, 2021)
Previous studies have found donkey milk (DM) has the similar compositions with human milk (HM) and could be used as a potential hypoallergenic replacement diet for babies suffering from cow's milk allergy. Milk fat globule membrane (MFGM) proteins are involved in many biological functions, behaving as important indicators of the nutritional quality of milk. In this study, we used label-free proteomics to quantify the differentially expressed MFGM proteins (DEP) between DM (in 4–5 months of lactation) and HM (in 6–8 months of lactation). In total, 293 DEP were found in these two groups. Gene Ontology (GO) enrichment analysis revealed that the majority of DEP participated in regulation of immune system process, membrane invagination and lymphocyte activation. Several significant Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were determined for the DEP, such as lysosome, galactose metabolism and peroxisome proliferator-activated receptor (PPAR) signaling pathway. Our study may provide valuable information in the composition of MFGM proteins in DM and HM, and expand our knowledge of different biological functions between DM and HM.